2023
DOI: 10.1097/cce.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompromised Children With Acute Respiratory Distress Syndrome Possess a Distinct Circulating Inflammatory Profile

Abstract: IMPORTANCE:Immunocompromised status, with and without stem cell transplant, confers a worse prognosis in pediatric acute respiratory distress syndrome. An improved understanding of the biochemical profile of immunocompromised children with acute respiratory distress syndrome would inform whether specific pathways are targetable, or merely bystanders, in order to improve outcomes in this high-risk subgroup. OBJECTIVES:We aimed to identify a biomarker profile of immunocompromised children, with and without stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, our associations were maintained even after adjustment for confounders and removal of immunocompromised patients, a group that when suffering from PARDS may be associated with a higher susceptibility to and degree of endothelial injury. 52,53 Taken together, these results suggest that EGCX degradation as reflected by increased concentrations of highly sulfated HS disaccharides and syndecan-1 may be in part associated with the sepsis-associated PARDS pathobiology. There remains an incomplete understanding of the key inflection points that mediate pulmonary microvascular endothelial dysfunction supporting an ongoing need to study the mechanistic role of EGCX degradation in children with PARDS.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, our associations were maintained even after adjustment for confounders and removal of immunocompromised patients, a group that when suffering from PARDS may be associated with a higher susceptibility to and degree of endothelial injury. 52,53 Taken together, these results suggest that EGCX degradation as reflected by increased concentrations of highly sulfated HS disaccharides and syndecan-1 may be in part associated with the sepsis-associated PARDS pathobiology. There remains an incomplete understanding of the key inflection points that mediate pulmonary microvascular endothelial dysfunction supporting an ongoing need to study the mechanistic role of EGCX degradation in children with PARDS.…”
Section: Discussionmentioning
confidence: 79%
“…However, our associations were maintained even after adjustment for confounders and removal of immunocompromised patients, a group that when suffering from PARDS may be associated with a higher susceptibility to and degree of endothelial injury. 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
“…During prone ventilation, the negative pressure in the thoracic cavity gradually decreased from the dorsal to the ventral, while the transpulmonary pressure decreased, resulting in a decrease in ventral ventilation, but it could still maintain the opening of ventral alveoli ( 30 ). At the same time, after the prone position, the lung lobe volume slightly increased compared with the supine position, the original anatomical position is located below the heart compressed by the heart to reduce the lung lobe volume increased, thus causing the collapse alveoli originally oppressed by the heart to re-expand ( 31 ). Through the comparison of lung tissue ventilation blood flow gradient between healthy volunteers and mechanically ventilated patients in different positions, it has been confirmed that the ventilation distribution increase slowly from ventral lung tissue to back when lying on the back, and suddenly decreased at the last 25% of the dorsal lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The biology of respiratory failure in immunocompromised children is complex. There have been efforts to identify underlying biomarkers in this population, which is a step toward better understanding the biologic causes 23,24 . However, currently bronchoscopy with extensive infectious workup and clinical expertise are the only widely available methods to diagnose causes of pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%